Patterns of palliative radiotherapy fractionation for brain metastases patients in New South Wales, Australia. (March 2021) - Batumalai, V.; Descallar, J.; Delaney, G.P.; Gabriel, G.; Wong, K.; Shafiq, J.; Vinod, S.K.; Barton, M.B.
Highlights: We assessed variation in palliative RT fractionation for brain metastases in an Australian population-based cohort. Only 51% of patients received <6 fractions of whole brain RT. Factors associated with shorter courses were older age, primary lung cancer, no surgical excision, and lower SES. Accelerating the uptake of shorter fractionation regimens, if warranted through evidence, should be prioritised. Abstract: Background and purpose: There is a paucity of studies examining variation in the use of palliative radiation therapy (RT) fractionation for brain metastases. The aim of this study is to assess variation in palliative RT fractionation given for brain metastases in New South Wales (NSW), Australia, and identify factors associated with variation. Materials and methods: This is a population-based cohort of patients who received whole brain RT (WBRT) for brain metastases (2009–2014), as captured in the NSW Central Cancer Registry. A logistic regression model was used to identify factors associated with fractionation type. Results: Of the 2, 698 patients that received WBRT, 1, 389 courses (51%) were < 6 fractions, 1, 050 courses (39%) were 6–10 fractions, and 259 courses (10%) were > 10 fractions. Older patients were more likely to be treated with shorter courses (P < 0.0001). Patients with primary lung cancers were more likely to receive shorter courses compared with other primary cancers (P < 0.0001). Patients without surgical excision were more likely to receive < 6 fractions compared to those who underwent surgical excision. Shorter courses were more likely to be delivered to patients with the most disadvantaged socioeconomic status (SES) compared with patients with the least disadvantaged SES (P < 0.0001). There were significant fluctuations in the proportion of courses using lower number of fractions over time from 2009 to 2014, but no apparent trend (P = 0.02). There was wide variation in the proportion of shorter courses across residence local health districts, ranging from 24% to 69% for < 6 fractions, 21% to 72% for 6–10 fractions, and 4% to 20% for > 10 fractions (P < 0.0001). Conclusion: This study has identified significant unwarranted variations in fractionation for WBRT in NSW. Accelerating the uptake of shorter fractionation regimens, if warranted through evidence, should be prioritised to enhance evidence-based care.